Evaluating protocols for normalizing forearm electromyograms during power grip - Ngo, B. P. T.; Wells, R. P. (Journal of Electromyography and Kinesiology, 2016)
Many studies use a reference task of an isometric maximum voluntary power grip task in a mid-pronated forearm posture to normalize their forearm electromyographic (EMG) signal amplitude. Currently there are no recommended protocols to do this. In order to provide guidance on the topic, we examined the EMG amplitude of six forearm muscles (three flexors and three extensors) during twenty different maximal voluntary efforts that included various gripping postures, force and moment exertions and compared them to a frequently used normalization task of exerting a maximum grip force, termed the reference task. 16 participants (8 male and 8 female, aged 18-26) were recruited for this study. Overall, maximal muscle activity was produced during the resisted moment tasks. When contrasted with the reference task, the resisted moment tasks produced EMG activity that was up to 2.8 times higher (p < 0.05). Although there was no one task that produced greater EMG values than the reference task for all forearm muscles, the resisted flexor and extensor moment tasks produced similar, if not higher EMG activity than the reference task for the three flexors and three extensor muscles, respectively. This suggests that researchers wishing to normalize forearm EMG activity during power gripping prehensile tasks should use resisted flexor and extensor moment tasks to obtain better estimates of the forearm muscles` maximum electrical activation magnitudes.